Investigating which behaviour change techniques work for whom in which contexts delivered by what means: Proposal for an international collaboratory of Centres for Understanding Behaviour Change (CUBiC). Issue 1 (20th October 2020) - Armitage, Christopher J.; Conner, Mark; Prestwich, Andrew; de Bruin, Marijn; Johnston, Marie; Sniehotta, Falko; Epton, Tracy
Abstract : Purpose: Behaviour change techniques are fundamental to the development of any behaviour change intervention, but surprisingly little is known about their properties. Key questions include when, why, how, in which contexts, for which behaviours, in what combinations, compared with what, and for whom behaviour change techniques are typically effective. The aims of the present paper are to: (1) articulate the scope of the challenge in understanding the properties of behaviour change techniques, (2) propose means by which to tackle this problem, and (3) call scientists to action. Methods: Iterative consensus (O'Connor et al., 2020, Br. J. Psychol ., e12468) was used to elicit and distil the judgements of experts on how best to tackle the problem of understanding the nature and operation of behaviour change techniques. Results: We propose a worldwide network of 'Centres for Understanding Behaviour Change' (CUBiC) simultaneously undertaking research to establish what are the single and combined properties of behaviour change techniques across multiple behaviours and populations. We additionally provide a first attempt to systematize an approach that CUBiC could use to understand behaviour change techniques and to begin to harness the efforts of researchers worldwide. Conclusion: Better understanding of behaviour change techniques is vital for improving behaviour change interventions to tackle global problems such as obesity and recovery from COVID‐19. The CUBiC proposal is just one of many possible solutions to the problems that the world faces and is a call to action for scientists to work collaboratively to gain deeper understanding of the underpinnings of behaviour change interventions.